2020
DOI: 10.3390/insects11070404
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evaluation of Breeding Scheme Alternatives for Endangered Honeybee Subspecies

Abstract: Modern breeding structures are emerging for European honeybee populations. However, while genetic evaluations of honeybees are becoming increasingly well understood, little is known about how selection decisions shape the populations’ genetic structures. We performed simulations evaluating 100 different selection schemes, defined by selection rates for dams and sires, in populations of 200, 500, or 1000 colonies per year and considering four different quantitative traits, reflecting different genetic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 87 publications
(133 reference statements)
4
34
0
Order By: Relevance
“…However, they do not account for inbreeding or genetic drift and therefore will always predict a linear genetic gain over time. Long-term simulation studies in honeybees and other species have shown that such a behavior over many generations is unrealistic [ 14 , 28 , 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, they do not account for inbreeding or genetic drift and therefore will always predict a linear genetic gain over time. Long-term simulation studies in honeybees and other species have shown that such a behavior over many generations is unrealistic [ 14 , 28 , 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the Bulmer effect, changes in genetic variance can also be caused by genetic drift, inbreeding, and mutation. The effects of these factors on honeybees have been investigated in various studies (Beye et al 2006 ; Plate et al 2019a , 2020 ; Zayed and Packer 2005 ). However, they will influence the genetic variance only over an extended period of time and not in the short time frame considered in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, they will influence the genetic variance only over an extended period of time and not in the short time frame considered in the present study. The initial gain of genetic variance in the performance and SC after the introduction of controlled mating could therefore become reduced over time as the selection of pseudo sires increases the risks of accumulated inbreeding and genetic drift (Plate et al 2019a , b , 2020 ). Furthermore, we mainly quantified the effects of controlled mating and selection to the immediate next generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The declining effective population size and loss of genetic diversity explained the main intrinsic factors for the endangerment of A. cerana in Changbai Mountain, and inbreeding has been shown to negatively affect traits such as nectar production and swarming behaviour [75]. Frequent queen breeding and colony trade activities promote gene flow between native and commercial populations; however, it yet may lead to irreversible loss of local adaptations in native populations, genetic homogenisation, and pose a risk of genetic contamination [76,77].…”
Section: Discussionmentioning
confidence: 99%